Measuring the Quality of Regional Development Planning from the Perspective of Bappenas Regulations - Agus Lukman Hakim; Natta Sanjaya; Ihyauddin; Hanifah; Siti Yuniar (Journal of Public Administration and Local Governance, 2026)
This study aims to measure the performance of development planning, which is manifested in an evaluation of the quality of regional planning documents (RPJMD and RKPD) along with planning documents at the regional apparatus level. This study uses a quantitative approach, namely by scoring the assessment of development planning documents with the content analysis method through document studies. The data used are predominantly secondary data sourced from various regional apparatuses in Serang Regency. Primary data is through field observations and unstructured interviews. The measurement method refers to the Circular Letter of the Minister of National Development Planning/Head of the National Development Planning Agency Number 3 of 2023 which includes: a) Integration of Regional Development Planning, b) Planning Quality, c) Connectedness of Development Planning with Performance Planning. The results of the study indicate that the regional development planning index of Serang Regency in 2025 obtained a score of 94.39 and is included in the very good category. The synergy dimension showed a score of 26.4 out of 32, with a note that there are still shortcomings in the aspect of alignment between the RKPD Document and the RKP. The planning quality dimension showed a maximum score of 58, reflecting the alignment of strategic issues with designed programs/activities and innovation in development planning. The planning-performance linkage dimension obtained a maximum score of 10, reflecting the alignment between development targets and the performance targets of related agencies. These findings are expected to serve as a strategic reference to optimize the quality of regional development planning in Serang Regency. The implication is the need to strengthen planning integration, increase institutional capacity, and optimize data-based monitoring, evaluation, and innovation.